Strategi Komunikasi Dakwah Da’i Salaf - Muhamad Taki Rumakat (Jurnal Peurawi: Media Kajian Komunikasi Islam, 2017)
This paper aims to explain the strategy of preaching da'i salaf communication, which by using methods or ways of gentle da'wah, to attract the attention of people following their da'wah. The way of da'wah da'i salafi is a dakwah that has been built since the Prophet sallallaahu 'alaihi Wa Salam with the Companions of the Prophet sallallaahu' alaihi Wa Salam in the city of Medina, the goal is to invite people to worship God and away from all the prohibitions of Allah, Human beings to mankind God, and away from the shirking deeds they do. So da'i salaf follow da'wah performed Prophet and the Companions with the aim to build da'wah as the Prophet runs. Keywords: communication strategy, da'wah, da'i salafi